Determinants and predictive modelling of barriers to HIV testing uptake among adolescents and young adults in a private higher education institution in Botswana - Gabalape Arnold Sejie; Thato Lebang; Gosego Ngole; Onneile Dichabe; Merapelo Selwane; Oratile Marapo; Kefilwe Madikwe; Goratang Malgas; Tumelo Ikaneng (PLoS ONE, 2026)
Background HIV represents a significant public health challenge, contributing to increased mortality and morbidity in developing countries, particularly Sub-Saharan Africa. While HIV testing is crucial for early treatment and prevention, the uptake of the HIV testing among the adolescent and young adults in Botswana remains low. This study aims to predict barriers to HIV testing uptake among adolescents and young adults. Method A quantitative cross-sectional study was conducted. Data was obtained using a questionnaire employing a simple random sampling technique to collect the survey data. Statistical analysis involved descriptive statistics and multivariable logistic regression. Results A total of 353 participants were recruited. The prevalence of HIV testing uptake in the preceding 12 months was (64.9%; n = 229). Determinants associated with non-uptake of HIV testing included participants in casual relationships (OR 1.776,95%CI 0.998–3.160, P < 0.049), transactional relationships (AOR 1.098, 95% CI 0.189–6.382) compared with single participants. Additional determinants included residence beyond 5 km from HIV testing centers (OR 1.825, 95% CI 1.074–3.103, P < 0.026), and cohabiting (AOR 3.45, 95% CI 0.271–43.979). Religious affiliation was also predictive, with Christians (AOR 2.347, 95% CI 0.188–29.295), Muslims (AOR 1.765, 95% CI 0.046–59.506), and adherents of African traditional religions (AOR 1.718, 95% CI 0.084–35.004) exhibiting higher odds of non-testing compared with non-believers. Participants with negative attitudes toward HIV testing were 69% less likely to forgo HIV testing (OR 0.310, 95% CI 0.1704–3.103, P = 0.026) than those with positive attitudes. Conclusion This study provides critical evidence on disparities in HIV testing among adolescents and young adults in Botswana, highlighting persistent gaps in access and utilization. These findings underscore the necessity for context-specific strategies that mitigate access barriers and address behavioral, structural, and socio-cultural determinants to optimize HIV testing uptake, advancing progress toward the UNAIDS 2030 target of zero new infections.